A Conceptual Framework on the Green Synthesis of Metal Nanoparticles using Soap Nuts - Nair Sivasankaran, Praveena; Shakila, Ainon; Sin Jin, Tan (International Journal of Engineering and Technology, 2019)
Green synthesis of nanoparticles has been an area of interest the past few years due to its promising growth. This conceptual framework paper explores the potential use of Sapindus Mukorossi or better known as soap nuts to be used as the reducing agent in synthesizing metal nanoparticles namely copper, silver and gold respectively. By exploring a greener method to synthesize nanoparticles, many potential application could be explored such as a green filtration technique to provide clean water to billions of people, the increased usage of renewable energy, the reduction of cost for waste management and to explore the possibilities of river reclamation. The usage of metal nanoparticles has been widespread across various fields hence, there is an urge to review its biological and environmental safety during its production. The main methods for nanoparticle production involves chemicals that are potentially harmful to the environment. The usage of plants to transform inorganic metal ions into metal nanoparticles with a capability of heavy metal and toxic accumulation has cultivated interest among researchers. Soap nuts are berries that have saponin as a natural surfactant and this research utilizes the fruits pericarp to synthesize copper, silver and gold nanoparticles. The production of nanoparticles will be studied for its effectiveness and the characteristics of the nanoparticles used for a future project which involves sustainability measures focusing on water filtration systems and river reclamation projects.Â